Governance Performance of Pokdarwis in Cipada Tourism Village, Cikalong Wetan Sub-District, West Bandung Regency - Ristanto, Hari; Sutono, Anang; Sumaryadi; Rahtomo, Wisnu; Permana, Odang (Journal of Tourism Sustainability, 2025)
Tourism villages are increasingly recognized as models of sustainable and community-based tourism; yet, their success largely depends on the effectiveness of governance. This study evaluates the governance performance of Pokdarwis (Tourism Awareness Groups) in Cipada Tourism Village, West Bandung Regency, from the perspective of visitor satisfaction. Using a quantitative descriptive design, data were collected from 105 visitors via structured questionnaires and analyzed using descriptive statistics. The findings reveal that visitors positively perceived the village's cultural uniqueness and environmental cleanliness, while infrastructure and informational signage were rated lower. Overall satisfaction, emotional happiness, and revisit intention were high, with hospitality and cultural immersion serving as the strongest drivers. Governance reflections suggest that Pokdarwis has been effective in mobilizing community participation and preserving cultural authenticity, but faces challenges in infrastructure provision and interpretive communication. The study concludes that visitor satisfaction serves not only as an outcome but also as a feedback mechanism for governance performance. Practical recommendations include improving infrastructure, enhancing interpretive communication, diversifying tourism products, and strengthening partnerships through the Penta Helix model. This research contributes to tourism governance literature by empirically linking visitor satisfaction to local governance performance in rural contexts.